The Enskog theory for self-diffusion coefficients of simple fluids with continuous potentials - Miyazaki, K.; Srinivas, G.; Bagchi, B. (Condensed Matter Physics, 2001)
We develop the Enskog theory for the self-diffusion coefficient for fluids with continuous potentials. General expressions for the memory kernel and the self-diffusion coefficient are derived starting from the Green-Kubo formula. The time-dependent memory kernel is calculated and compared with molecular dynamics simulations for the Lennard-Jones fluid. Excellent agreement is obtained at low density. The self-diffusion coefficient is evaluated for several temperatures and densities. The ratio of the Enskog self-diffusion coefficient to the simulation value is plotted against density for the Lennard-Jones fluid. Significant difference of this density dependence from that for the hard-sphere fluid is observed. In particular, the well-known maximum observed in the hard-sphere fluid is found to be completely absent in the Lennard-Jones fluid.